Ultrasonic Velocity and Thermoacoustic Parameters for Copper(I) Nitrates in Dimethylsulfoxide with Pyridine as a Co-Solvent at 298 K - Pathania, Vivek; Kaur, Manpreet; Vermani, Bal K.; Anand, Veneeta; Gill, Dip Singh (Current Physical Chemistry, 2022)
Aims: This study aimed to explore the ultrasonic velocity and thermoacoustic parameters for copper(I) nitrates in dimethylsulfoxide with pyridine as a co-solvent at 298 K. Background: Ultrasonic velocity variation and related factors provide a plethora of information regarding the acoustic behaviour of solutions. These studies help in understanding various kinds of interactions like ionic interactions in electrolytic solutions, molecular interactions in liquidliquid mixtures, and solute-solvent interactions. Objective: The objective of this study was to estimate the density (ρ) and ultrasonic velocity (u) of copper (I) nitrate complexes in the concentration range of 0.02-0.28 m.Kg-1 in dimethylsulfoxide (DMSO), pyridine (Py), and binary mixtures of DMSO+Py having 0, 20, 40, 60, 80, and 100-mole percentage of Py at 298 K and 1 atmospheric pressure. The study also aimed to determine the isentropic compressibility (Κs) and apparent molal isentropic compressibility (Κs,ø ) (which is the degree of electrostatic force occurring in solution) of various salts in the binary solvent mixtures using density values and ultrasonic velocities. Methods: Using long borosilicate glass tubes, the DSA 5000 M from Anton Parr was utilized to measure the density and ultrasonic velocity at 298 K operating at a frequency of 2 MHz. Results: The apparent molal isentropic compressibility (Κs,ø) of the electrolytes was divided into the contributions of individual ions (Κos,ø)±. As the composition of the co-solvent increases, the (Κos,ø)± values for Cu (I) ions fall, i.e., they become more negative in magnitude. The (Κos,ø)± values for Bu4N+, Ph4B-, ClO4 -, and NO3 - are positive but decrease as they move to Py-rich regions. Strong structural effects due to interactions between solute-solute and solvent-solvent are indicated by negative (Κos,ø)± values. Thus, solvation increases in Py-rich regions. Furthermore, thermoacoustic parameters were evaluated from the experimentally measured values. The results were associated in terms of molecular interaction between the solute and the solvent, demonstrating that solutes have the potential to break or make structures with solvents. Conclusion: Experimental measurements of density (ρ), and ultrasonic velocities (u) in DMSO+Py at 298 K revealed that Κos#149; value for the copper(I) nitrates like [Cu(AN)4]+, [Cu(Phen)2]+ , [Cu(BN)4]+ [Cu(DMPhen)2]+ , [Cu(Bipy)2]+ , [Cu(TU)4]+, and the reference electrolyte decreases (less positive) or becomes more negative as the mole percentage of co-solvent increases. The Κos#149; values were further split to find the value of individual ions. The (Κos,ø)± values for Bu4N+, Ph4B-, ClO4 -, and NO3 - are positive but also show a decreasing trend in Py-rich regions. A negative (Κos,ø)± value indicates the presence of strong structural effects in the solvent mixture on the addition of electrolytes. Results show that solvation increases in Py-rich regions. Further correlating acoustic parameters in terms of molecular interactions also favored trends in the solvation behaviour of electrolytes. The increase in the value of Z depicts the formation of the H bond, which results in strong solute-solute interactions. The values of Κs and Lf decreased as concentration increased for all the electrolytes, indicating a significant structure-forming tendency of copper(I) electrolytes in Py-rich locations. The value of RA also increases as the composition of the co-solvent increases, indicating stronger solvation behaviour in Py rich region. Lf and Τ decreased as concentration increased for all the electrolytes, indicating strong interactions between the molecules of electrolytes with the solvent in Py-rich regions.
Keywords: isentropic compressibility